2003
DOI: 10.1021/nl0340935
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated CdSe Nanocrystals as Nanosensors for Gases

Abstract: The photoluminescence (PL) of high-quality CdSe nanocrystals (NCs) incorporated into polymer thin films was found to respond reversibly and rapidly to environmental changes upon photoradiation above their absorption onset. The PL of the NCs may be dramatically enhanced or diminished depending on the properties of the gases. Photostimulation was found to be necessary for the response, which likely makes the original dense-ligands monolayer on the surface of the NCs permeable to gases by the activation of the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
205
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(212 citation statements)
references
References 18 publications
7
205
0
Order By: Relevance
“…CdSe is one of such materials, shows strong fluorescence which can be tuned according to the particle size. CdSe has been considered in many applications such as optoelectronic devices (Nazzal et al 2003), light sensors (Bruchez et al 1998), biological labels (Colvin et al 1994), chemical libraries (Gaponik et al 2002), etc. The nanopowder of CdSe provides excellent and unique properties which depend upon the shape and size of the nanostructures (Haram et al 2001;Wang et al 2004;Datta and Das 1990;Peng et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…CdSe is one of such materials, shows strong fluorescence which can be tuned according to the particle size. CdSe has been considered in many applications such as optoelectronic devices (Nazzal et al 2003), light sensors (Bruchez et al 1998), biological labels (Colvin et al 1994), chemical libraries (Gaponik et al 2002), etc. The nanopowder of CdSe provides excellent and unique properties which depend upon the shape and size of the nanostructures (Haram et al 2001;Wang et al 2004;Datta and Das 1990;Peng et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The suited PL properties include broad absorption band, size tuneable spectral emission, higher photostability, and emission lifetime ranging between several hundreds of picosecond and tens of nanosecond [6]. In the last ten years, authors reported the sensitivity of colloidal QDs embedded into polymeric matrix [7][8][9][10][11], sol-gel materials [12,13] or dispersed in Al 2 O 3 nanopore array [13]. Per se they display sensitivity towards some commonly used solvents like methanol, ethanol, acetone and chloroform [12].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional organic dyes, QDs have excellent optical properties: a wider absorption band and a narrower emission band of mostly symmetric shape [53]. In 2003, Peng's research group [54] proposed that semiconductor NCs can be used as the gas sensing material, because gas can cause a weak change of chemical or physical properties on NCs surface, and it thus changes the optical properties. CdSe NCs incorporated into polymer thin films was found a better response for amines.…”
Section: Sensorsmentioning
confidence: 99%